Development of Gold-PAGE: towards the electrophoretic analysis of sulphurous biopolymers. Issue 34 (31st July 2019) - Taylor, Emerald R.; Cavuoto, Silvia; Beal, David M.; Caujolle, Sophie; Podoleanu, Adrian; Serpell, Christopher J.
Abstract : Gold nanoparticles, encapsulated within polyacrylamide electrophoresis gels, can discriminate between number of type of sulphur modifications in DNA strands. Abstract : The prevalence, distinctive reactivity and biological significance of sulphur-based groups in proteins and nucleic acids means that analysis of sulphur is of prime importance in biochemistry, biotechnology, and medicine. We report steps in the development of a method to aid in the detection of these moieties using gold nanoparticles as adjuncts in polyacrylamide gel electrophoresis (Gold-PAGE).